Modelagem numérica-experimental da produção de sedimentos de pequenas bacias hidrográficas da Amazônia - BARBOSA, Ana Júlia Soares da Silva (Universidade Federal do Pará, 2021)
Erosion is a process of direct impact in urban and rural environments. The understanding of this process requires the use of models and techniques of geoprocessing and field, for approximate estimation of the realized one, since it is a phenomenon with many variables to be taken into account. For the present study, two models were used to generate data in a small Amazon basin. The USLE (universal soil loss equation) and also the modified MUSLE version. For both models, the common factors (K, LS, C and P) were determined. For USLE, the calibration occurred for rain erosivity, which is the differential factor of this model. After USLE application with calibrated R factor, the model was applied to the study area with an average soil loss of 1.99 ton. ha-1.year-1, for a period of 21 years. For MUSLE, the differential variables are the hydrological variables (Q and qp) were determined by analyzing the hydrographs observed with the aid of a digital filter. Two methods of calibration and validation have been done for MUSLE. Method 1 calibrated the factors ɑ and b, with sediment production data measured from 62 flood events from 2012 to 2014. The values found for factors ɑ and b were equal to 19.90 and 0.60, respectively. MUSLE was validated with sediment production data measured from 62 flood events in the years 2014 and 2015. The validated MUSLE equation represented in a satisfactory way, in more than 70%, the data of soil loss observed in the hydrographic basin of the Igarapé da Prata. Method 2 calibrated only the value of a, using the solid discharge curve with potential regression for the years 2012 and 2013, which showed R² of 0.70 and 0.68, respectively. The value of ɑ obtained was 17.25, and was applied to MUSLE, keeping the value of b at 0.56, the original value of the model. The validation for the latter method proved to be adequate, with an R² of 0.69. These results validate the empirical models for the region with experimental activities, which corroborates for the production of sediment information in the Amazon region, as a way of maturing and the search for new research, for the understanding of the impacts arising from the transport of soil between areas and in the water environment.